KREASI, INOVASI, DAN PROMOSI BATIK â€œPEâ€ (PITHECANTHROPUS ERECTUS) SEBAGAI CENDERA MATA WISATA ICONIC KABUPATEN NGAWI - Margana, Margana; Setiyoko, Nanang; Sugiarti, Rara (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2020)
UKM Batik Anisa encounters several problems including limited creativity and innovation to create new designs and iconic motifs that can represent regional characteristics, limited variations in batik color, limited market network, marketing strategies, and promotional media for batik products, limited knowledge about tourism and the important role of souvenir, and limited tools and materials that are relevant for initiating the development of new batik motif called pithecanthropus erectus (PE). This is innovative motif that has the potential to become iconic batik product of Ngawi. This activity aims to overcome problem faced by UKM Batik Anisa. Methods include counseling, discussing, training, and assisting. Results of the activity include innovations of new batik design and motifs (pithecanthropus erectus), variation of batik color through diverse combination of color, website to expand market networks, knowledge improvement concerning tourism and opportunities to create iconic souvenirs, and new tools to increase productivity of UKM Batik Anisa.Â Keywords: batik; design; iconic; pithecanthropus erectus.